Factors that influence primary school teachers when sending homework to students in the Region of Murcia (Spain) - Cascales-Martínez , Antonia; Pamies-Berenguer , Marcial; Carrillo-García, María Encarnación (Revista Portuguesa de Educação, 2021)
The aim of this article is to define factors that influence elementary school teachers when assigning homework to students. The study was conducted with a sample of 93 teachers of the Region of Murcia (Spain). Teachers answered a questionnaire, with 35 questions, that was validated through an expert judgment by the Angoff method (Ricker, 2006). The analysis of data defined the factors, and they were: Family Involvement, Personal Feelings, Staff Decisions and Assumptions. Besides, the variables defined as frequency of homework, activities per week and needed to do homework, help us to conclude that there were decisive factors for teachers when giving homework to their students, and these factors were conditioned by the number of days per week that teachers assign tasks to their students, the estimated number of activities per week given to students, and the time needed to complete the tasks.